Change in the Lipid Transport Capacity of the Liver and Blood during Reproduction in Rats - Zhang, Yufeng; Kallenberg, Christine; Hyatt, Hayden W.; Kavazis, Andreas N.; Hood, Wendy R. (Frontiers in Physiology, 2017)
To support the high energetic demands of reproduction, female mammals display plasticity in many physiological processes, such as the lipid transport system. Lipids support the energy demands of females during reproduction, and energy and structural demands of the developing offspring via the placenta in utero or milk during the suckling period. We hypothesized that key proteins supporting lipid transport in reproductive females will increase during pregnancy and lactation, but drop to non-reproductive levels shortly after reproduction has ended. We compared the relative protein levels of liver-type cytosolic fatty acid transporter (L-FABPc), plasma membrane fatty acid transporter (FABPpm), fatty acid translocase (FAT/CD36) in the liver, a key site of lipid storage and synthesis, and free fatty acid transporter albumin and triglyceride transporter (represented by apolipoprotein B (apoB)) levels in serum in reproductive Sprague-Dawley rats during late pregnancy, peak-lactation, and 1-week post-lactation as well as in non-reproductive rats. We found that all lipid transporter levels were greater in pregnant rats compared to non-reproductive rats. Lactating rats also showed higher levels of FAT/CD36 and FABPpm than non-reproductive rats. Moreover, all fat transporters also dropped back to non-reproductive levels during post-lactation except for FAT/CD36. These results indicate that fat uptake and transport capacities in liver cells are elevated during late gestation and lactation. Liver lipid secretion is upregulated during gestation but not during lactation. These data supported the plasticity of lipid transport capacities in liver and blood during reproductive stages.